Detection of gastric cancer with implantation metastasis to the inguinal region via 18F-FAPI PET/CT: a case report - Zhang, Haibo; Hao, Shanhu; Wu, Tong; Wu, Zhongbao; Liu, Xuantong; Xu, Ying; Zhang, Peng; Yan, Ying (Frontiers in Oncology, 2025)
Implantation metastasis of gastric cancer to the inguinal area is rarely reported, and a clear diagnosis of such metastasis is hard to make, especially when these cancers are invisible on fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) imaging. However, certain types of cancers, such as signet-ring cell carcinoma, are particularly sensitive to fibroblast activation protein inhibitor (FAPI) PET/CT. In this case, a patient with a history of gastric cancer and a gastrectomy 2 years previously suddenly developed serious edema in his right lower limb. With the help of FAPI PET/CT and other laboratory findings, abdominal implantation of his primary gastric cancer to the inguinal region was confirmed. After prompt treatment, the patient had a favorable prognosis.